Music-evoked autobiographical memories, emotion regulation, time perspective, and mental health. (March 2016) - Blais-Rochette, Camille; Miranda, Dave
The intriguing phenomenon by which songs trigger the recall of self-defining moments in one's past is called music-evoked autobiographical memories (MEAMs). This study examines if various types of MEAMs can partially mediate the impact that emotion regulation (reappraisal and suppression) and time perspective (past positive and past negative) can have on mental health (internalizing symptoms and happiness) in youth. To this end, we developed the Music Evoked Memory Orientation Scale (MEMOS), which was specifically designed to assess the phenomenological characteristics of MEAMs. The sample consisted of 397 undergraduate students (Mage = 19.17 years; 80.6% female) that attended a Canadian university. Results revealed that the MEMOS had adequate psychometric qualities in terms of factorial validity, internal consistency, convergent validity, and incremental validity. Most notably, analyses indicated that social sharing of MEAMs mediated the relationships between emotion regulation (reappraisal and suppression) and happiness. However, aspects of MEAMs (self-identification, social sharing, and coherence) did not mediate any relationship between emotion regulation and internalizing symptoms. Also, of particular interest, social sharing of and coherence in MEAMs mediated the relationships between past positive and mental health. However, aspects of MEAMs (self-identification, social sharing, and coherence) did not mediate relationships between past negative and mental health. Interestingly, mediated effects from MEAMs held despite controlling for personality traits (Extraversion and Emotional Stability). In sum, future studies need to examine why only some MEAMs, particularly the social sharing of MEAMs, matter at the intersection of emotion regulation, time perspective, and mental health in youth.